Effects of Choice Architecture Strategies on Lower-Sugar Beverage Selection among Public Health Students: A Quasi-Experimental Study - Jaroenbunpol, Pornthip; Songwaja, Walaitip; Phonwetamnuai, Subhawita; Teeweang , Suthasinee; Sornplang, Adithep; Boonchoo, Wannachanok (Journal of Nutrition Association of Thailand (Online), 2026)
Consumption of sugar-sweetened beverages is a major contributor to excessive sugar intake and increases the risk of non-communicable diseases. This study aimed to evaluate the effectiveness of choice architecture strategies on beverage selection among students of the Faculty of Public Health, Mahidol University. A repeated-measures quasi-experimental study was conducted among 49 participants. Each participant selected Thai tea beverages under three experimental conditions: (1) a default low-sugar option, (2) sugar-content labels displayed in grams, and (3) sweetness-level labels displayed as percentages. The results showed that all three choice architecture strategies increased the proportion of lower-sugar beverage selections compared with participants’ usual choices. The default low-sugar option produced the highest proportion of lower-sugar selections (83.67%). Both the default low-sugar option and sugar-content labels significantly increased the selection of lower-sugar beverages compared with usual choices (p < 0.001 and p = 0.007, respectively). However, no statistically significant differences were observed among the three intervention strategies. These findings suggest that choice architecture strategies, particularly default options, may be a promising approach to promoting lower-sugar beverage choices among university students.